2022
DOI: 10.3389/fnbeh.2021.779080
|View full text |Cite
|
Sign up to set email alerts
|

High-Salt Diet in the Pre- and Postweaning Periods Leads to Amygdala Oxidative Stress and Changes in Locomotion and Anxiety-Like Behaviors of Male Wistar Rats

Abstract: High-salt (HS) diets have recently been linked to oxidative stress in the brain, a fact that may be a precursor to behavioral changes, such as those involving anxiety-like behavior. However, to the best of our knowledge, no study has evaluated the amygdala redox status after consuming a HS diet in the pre- or postweaning periods. This study aimed to evaluate the amygdala redox status and anxiety-like behaviors in adulthood, after inclusion of HS diet in two periods: preconception, gestation, and lactation (pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 86 publications
3
14
0
Order By: Relevance
“…Rearing frequency is the frequency with which the rodent stands on its hind legs in the open field, which might be a direct measure of anxiety [ 71 , 72 , 81 , 82 ]. We observed that the frequency of rearing was significantly higher in the Ko group than in the WT rats ( Ko : Mean = 36.50, SD = 6.48; WT : Mean = 18.84, SD = 4.18; p < 0.001) ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rearing frequency is the frequency with which the rodent stands on its hind legs in the open field, which might be a direct measure of anxiety [ 71 , 72 , 81 , 82 ]. We observed that the frequency of rearing was significantly higher in the Ko group than in the WT rats ( Ko : Mean = 36.50, SD = 6.48; WT : Mean = 18.84, SD = 4.18; p < 0.001) ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We also determined the total distance traveled (in cm) as an index of locomotor activity. In addition, the rearing frequency was used as a measure of exploratory behavior and anxiety [ 71 , 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that the consumption of an HSD is positively correlated with increased hypertension (Choi et al, 2015), cardiovascular diseases (Mozaffarian et al, 2014; Powles et al, 2013), and other health problems (Pajtok et al, 2021; M. Wang, 2020). Notably, most of these adverse consequences have a common pathological condition: excess generation of reactive oxygen species (ROS) and an insufficient antioxidant capacity (Ge et al, 2017; Geisberger et al, 2021; Leal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Wang, 2020). Notably, most of these adverse consequences have a common pathological condition: excess generation of reactive oxygen species (ROS) and an insufficient antioxidant capacity (Ge et al, 2017;Geisberger et al, 2021;Leal et al, 2021).…”
mentioning
confidence: 99%
“…These include specific subregions of the cingulate and prefrontal cortices, hippocampus, amygdala, and brainstem nuclei (e.g., locus coeruleus). Growing evidence indicates the hippocampus and amygdala are affected by excess salt consumption in rodents 2937 , while other brain regions remain underexplored. This evidence, combined with human evidence of comorbidity between anxiety disorders and cardiovascular diseases, supports our hypothesis – at least based upon male data – that fear generalization is augmented by high salt intake.…”
Section: Introductionmentioning
confidence: 99%